Pengaruh employee engagement terhadap financial performance dengan tingkat customer satisfaction sebagai faktor mediasi pada hotel mewah ABC di bilangan Jakarta Selatan - Raymond Obert Sanjaya; Yanuar Yanuar (Universitas Tarumanagara, 2023)
This study aims to determine the influence of employee engagement on financial performance mediated by customer satisfaction. The number of samples in this study was 154 respondents, all of whom were employees working at one luxury hotel in South Jakarta and customers who had experience living or conducting meetings & events at the hotel. This study uses a quantitative approach. The research data were obtained from the results of filling out the questionnaire and were analyzed quantitatively using the SEM-PLS analysis technique with the help of the SmartPLS program. The conclusions obtained from the results of this study are: (1) Employee engagement is proven to be a factor that significantly influences customer satisfaction; (2) Employee engagement is proven as a factor that significantly influences financial performance; and (3) Financial performance is proven as a factor that significantly influences customer satisfaction. Penelitian ini bertujuan untuk pengaruh employee engagement terhadap financial performance dengan dimediasi oleh customer satisfaction. Jumlah sampel dalam penelitian ini adalah sebanyak 154 responden yang seluruhnya merupakan karyawan yang bekerja di hotel mewah ABC di daerah Jakarta Selatan dan tamu yang memiliki pengalaman tinggal atau melakukan rapat serta acara di hotel-hotel. Penelitian ini menggunakan pendekatan kuantitatif. Data penelitian diperoleh dari hasil pengisian kuesioner dan dianalisis secara kuantitatif dengan menggunakan teknik analisis SEM-PLS dengan bantuan program SmartPLS. Kesimpulan yang diperoleh dari hasil penelitian ini adalah: (1) Employee engagement terbukti sebagai faktor yang secara signifikan memengaruhi customer satisfaction; (2) Employee engagement terbukti sebagai faktor yang secara signifikan memengaruhi financial performance; dan (3) Financial performance terbukti sebagai faktor yang secara signifikan memengaruhi customer satisfaction.